Pengaruh Latihan Split Jump terhadap Kecepatan Tendangan Depan Pencak Silat Pagar Nusa Pondok Pesantren Salafiah Darul Barokah - Wahyu Saputra, Nico; Maulana Putra, Ikhsan; Wulandari, Titis (Jurnal Muara Olahraga, 2025)
This study sought to ascertain the impact of split jump training on pencak silat competitors' front kicking proficiency. This study blended quantitative techniques with an experimental methodology. A pretest-posttest design with a single group was used. Purposive sampling was utilized to establish a sample size of 15 from the 38 athletes in the research population. Data collection was conducted through a pretest and posttest for the athletes' front kicking abilities. Data analysis involved two stages: (a) data normality testing to ensure data distribution, and (b) a paired-sample t-test to identify significant changes between pretest and posttest data. According to the study's findings, the posttest score was greater than the pretest, averaging 21.60 with a standard deviation of 2.02. The results of the normality test indicated that the data had a normal distribution (Sig. > 0.05). With an average rise of 2.87 points and a significance value of 0.000 (<0.05), the paired sample t-test findings demonstrated a significant difference between the pretest and posttest scores. This demonstrates that split jump training significantly improves Pagar Nusa pencak silat athletes' front kick speed.